Genetic analyses of the endocannabinoid pathway in association with affective phenotypic variants. (23rd January 2021) - Lazary, Judit; Eszlari, Nora; Kriko, Eszter; Tozser, Dora; Dome, Peter; Deakin, J. F. William; Juhasz, Gabriella; Bagdy, Gyorgy
Highlights: This is the first study of genetic pathway analysis of the endocannabinoid system on the affective phenotype. CACNA1C gene in interaction with childhood trauma yielded replicated associations in two samples. Between the eCB and CREB-BDNF pathways L-type voltage gated calcium channel can be an important linking effector. Childhood trauma together with CACNA1C variants can create a distinct subtype of affetcive disorders. Depressive disorders with childhood trauma is higher genetically determined than other etiopathological subtypes. Abstract: Backgorund: Increasing experimental data confirm the crucial role of the endocannabinoid (eCB) system in the regulation of stress response and emotional processes. Despite of the fact, that genetically determined vulnerability for stress is a widely accepted concept in the pathomechanism of affective disorders, replicable human genetic results with interaction analyses of early life trauma and eCB genes are rare. The aim of this study is to test the associations between genetic variants of the eCB pathway, childhood trauma and affective phenotypes. Methods: We selected 18, 897 SNPs in the eCB pathway of a GWAS dataset in two general population cohorts (BP sample N = 837; MN sample N = 988). Association analyses were performed on the anxious and depressive subscales of the Brief Symptom Inventory (BSI-ANX and BSI-DEP, respectively). Childhood trauma was assessed by the Childhood Adversity Questionnaire (CAQ). Association analyses were performed in the R 2.0. statistical program using the SNPassoc package. Reults: Genetic effect was more robust in the BP sample than in the MN sample. The most comprehensive results showed that SNPs in the CACNA1C gene associated with depressive phenotype in interaction with CAQ in both BP ( p = 1.2 × 10 −4 ) and MN samples ( p = 1.6 × 10 −4 ). Direct association analyses (without interaction) provided significant associations between SNPs in different genesets of the two study populations. SNPs in KCNJ3 and GNB5 genes on the BSI-DEP (p = 6.1 × 10 −5 ; p = 7.1 × 10 −4 ) and GNG12 gene on the BSI-ANX (p = 7.4 × 10 −6 ) in the BP sample, while GABAergic, ADCY1 and HTR2A gene variants can be outlined from results of MN sample with less strong p-values. Conclusion: Our results confirmed the prominent role of CACNA1C gene in the pathogenic effect of early life stress in the development of affective vulnerability in two different study populations using GxE interaction analysis. CACNA1C gene, as it encodes for L-type voltage-gated calcium channel, contributes to neuronal excitability, plasticity and neurogenesis being a crucial effector of both eCB signaling and the BDNF-CREB pathway as well. Our findings suggest that childhood trauma related depression may have more robust genetically determined basis than without early life stress.